Multimodal Digital X-ray Scanners with Synchronous Mapping of Tactile Pressure Distributions using Perovskites - Jang, Jiuk (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 The Authors. Advanced Materials published by Wiley-VCH GmbH.